Unusual Case of Severe Lactic Acidosis in a Liver Transplant Patient - Shweta Yemul Golhar; Michael S. Green; Stephen Guy (Case Reports in Transplantation)
Lactic acidosis is a standard indicator for oxygen debt and some other very significant causes. We describe a case of liver transplant patient presenting with vague abdominal pain and lactic acidosis without any liver dysfunction/failure/ischemia/rejection or sepsis. The imaging studies showed vague bowel edema and normal hepatic perfusion. The patient continued to deteriorate with rising lactic acidosis when a repeat CT abdomen eventually showed signs of lymphomatosis peritonei. Biopsy revealed the unusual diagnosis of posttransplant lymphoproliferative disorder. Immediate discontinuation of immunosuppression and initiation of chemotherapy led to clinical improvement. Our intention of presenting this case is to increase awareness of posttransplant lymphoma and propose lactic acidosis as not only an indicator of liver dysfunction or rejection but also an aid for diagnosis of this unusual but fatal and potentially curable condition.